Circular-hyperbolic Fibonacci quaternions - Aydin, Fugen Torunbalci (BULGARIAN ACAD SCIENCE, 2020)
In this paper, circular-hyperbolic Fibonacci numbers and quaternions are defined. Also, some algebraic properties of circular-hyperbolic Fibonacci numbers and quaternions which are connected with circular-hyperbolic numbers and Fibonacci numbers are investigated. Furthermore, Honsberger's identity, the generating function, Binet's formula, d'Ocagne's identity, Cassini's identity, and Catalan's identity for these quaternions are given.
Keywords: Fibonacci number; Hyperbolic number; Dual-hyperbolic number; Circular-hyperbolic number; Circular-hyperbolic Fibonacci number; COMPLEX FIBONACCI; LUCAS-NUMBERS; Mathematics